Buy, collect and stay fashionable: reflections on child consumption and the play - Fernanda Theodoro Roveri; Carmen Lúcia Soares (Universidade Federal de Santa Catarina, 2015)
Toys and other consumption articles are offered to children with the objective of suggesting desires of possession, distinction and social belonging to them. Advertising tries to condition behaviors to the style of the product, causing boys and girls to face a mediatic universe ruled by idols and fashion stars. These, in turn, bring indications of femininity and masculinity when they transmit life styles and goods. This article chooses Barbie doll for a discussion about childhood trying to reflect about behavior and body patterns taught to children. The target is then to discuss ideals of consumption, femininity and pleasure introduced by that doll, one of the childhood icons of girls from all around the world.